The Governance of Globalization: The Political Economy of Anglo-American Hegemony, 1793-2003 - Patrick K. O'Brien (Center for Economic Studies and ifo Institute (CESifo), 2003)
Modern globalization (which includes free flows of trade and factors of production across frontiers, stable rates of exchange, the containment of warfare and mercantilism, the preservation of the environment and latterly the protection of cities against rogue states and terrorism) are among the public goods provided for the world economy as a whole are represented as a beginning outcome of 6 decades of hegemony exercised by governments in Washington from l941 to 2003. The view promulgated largely by Anglo-American social scientists that the United Kingdom (and before that other powers) also supplied significant public goods for the international order has been degraded in this paper into theory without history. In short the assertion that American Hegemony can be perceived as a succession to the Pax Britannica from l793-l914 is virtually a myth.
Keywords: 330